Perancangan Pemodelan Unified Modeling Language Sistem Antrian Online Kunjungan Pasien Rawat Jalan pada Puskesmas - John Friadi; Dodi. P Yani; Muhammad Zaid; Alexsandri Sikumbang (Penerbit Goodwood, 2023)
Purpose: Puskesmas is the technical implementation unit of the district/city health service responsible for administering health services in its working area. One of the services at Puskesmas is the polyclinic for outpatient visits, where patients come and register at the designated polyclinic and obtain a visit queue number. Currently, registration of outpatient visits at the Puskesmas is still mostly done conventionally by coming to the Puskesmas to take a queue number so that the patient's time is wasted waiting to be called, which is burdensome for the patient's condition when the patient is sick. To overcome this, it is necessary to create an online queuing system for outpatient visits to make the queuing process less time-consuming and help patients save time, especially when they are sick. Methodology: This study focuses on developing a modeling method for designing information systems using unified Modelling Language (UML) diagrams. Results: The results of this study used case diagrams and class diagrams for modeling online queuing systems for patient visits in Puskesmas. It can be used during the application program development and implementation stage of an online queuing system for outpatient visits in Puskesmas. Limitations: This research is only for designing and developing guidelines for patient online queuing system applications. Contribution: This research contributes to the program to develop an online patient queuing system application for an android smartphone-based health centre.